Tax clientele effects in the German bond market - Richard Stehle; Stefan R. Jaschke; S. Wernicke (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
This paper presents an analysis of tax clientele eects in the German government bond market from the viewpoint of private investors. The methods developed here allow the identification of bonds that are over-valued from the viewpoint of a certain tax class, the estimation of tax-specific term structures, and the identification of representative investors. Regression and no-arbitrage approaches are unified. The empirical results presented have important implications for the estimation of the term structure from coupon bond prices and the valuation of interest rate derivatives.
urn:nbn:de:kobv:11-10056454
Keywords: E43; C14; C61; 330; linear programming; duality theory; term structure of interest rates; smoothing splines; tax clientele; arbitrage bounds